# the value of (a+b)^6

## Answers

Answered by

1

lIt is special case for Newton’s binomial formula:

(x+y)n…(1)

when x=a , y=−b and n=6 . Therefore, the expansion of (a−b)6 will be:

(a−b)6=

a6−6(a5)b+15(a4)(b2)−20(a3)(b3)+15(a2)(b4)−6a(b5)+b6

The formula can also be extracted by ((a−b)3)2 :

((a−b)3)2=(a3−3(a2)b+3a(b2)−b3)2=

[(a3–3(a2)b)+(3a(b2)−b3)]2=

[(a3−3(a2)b)]2+[(3a(b2)−b3)]2+2[(a3−3(a2)b)][(3a(b2)−b3)]=

a6−6(a5)b+15(a4)(b2)−20(a3)(b3)+15(a2)(b4)−6a(b5)+b6

U can just put a '+' instead of '-'

Similar questions